Long-term hip loading in unilateral total hip replacement patients is no different between limbs or compared to healthy controls at similar walking speeds. (26th October 2018) - O'Connor, John D.; Rutherford, Megan; Bennett, Damien; Hill, Janet C.; Beverland, David E.; Dunne, Nicholas J.; Lennon, Alex B.
Abstract: Variation in hip joint contact forces directly influences the performance of total hip replacements (THRs). Measurement and calculation of contact forces in THR patients has been limited by small sample sizes, wide variation in patient and surgical factors, and short-term follow-up. This study hypothesised that, at long-term follow-up, unilateral THR patients have similar calculated hip contact forces compared to controls walking at similar (self-selected) speeds and, in contrast, THR patients walking at slower (self-selected) speeds have reduced hip contact forces. It was further hypothesised that there is no difference in calculated hip contact forces between operated and non-operated limbs at long-term follow-up for both faster and slower patients. Gait analysis data for THR patients walking at faster (walking speed: 1.29 ± 0.12 m/s; n = 11) and slower (walking speed: 0.72 ± 0.09 m/s; n = 11) speeds were used. Healthy subjects constituted the control group (walking speed: 1.36 ± 0.12 m/s; n = 10). Hip contact forces were calculated using static optimisation. There was no significant difference (p > 0.31) in hip contact forces between faster and control groups. Conversely, force was reduced at heel strike by 19% (p = 0.002), toe-off by 31% (p < 0.001) and increased at mid-stance by 15% (p = 0.02) for the slower group compared to controls. There were no differences between operated and non-operated limbs for the slower group or the faster group, suggesting good biomechanical recovery at long-term follow-up. Loading, at different walking speeds, presented here can improve the relevance of preclinical testing methods.